Incorporation of diagnostic laparoscopy in the management algorithm for patients with peritoneal metastases: A multi‐institutional analysis. Issue 8 (3rd June 2015) - Tabrizian, Parissa; Jayakrishnan, Thejus T.; Zacharias, Anthony; Aycart, Samantha; Johnston, Fabian M.; Sarpel, Umut; Labow, Daniel M.; Turaga, Kiran K.
<x xml:space="preserve">Abstract</x> Introduction Diagnostic laparoscopy (DL), which can predict complete cytoreduction (CC), is often considered unfeasible in patients with Peritoneal metastases (PM) due to a hostile abdomen, prior surgeries, incomplete assessment or risk of port site recurrence. We hypothesized that DL can be successfully incorporated into the management of patients with PM. Methods Retrospective review and data analysis of prospectively maintained databases from two high volume institutions was performed between 2007 and 2013. Results DL was successfully completed in 211/217 (92.6%) patients with PM. The technique for entry was the Hasson in 57%, optical trocar in 38% and Veress needle in 5%. Serosal injury from DL occurred in one patient (0.4%). Predominant histology included appendiceal (40%) and colorectal primaries (34%). Exclusion from cytoreduction by DL occurred in 68 (31.3%). Among those excluded, 7 (of 68, 10.3%) subsequently underwent CRS + HIPEC after receiving systemic chemotherapy. Overall survival (from laparoscopy) for those that underwent CRS + HIPEC at the original operation was 36 versus 12.7 months among those who were excluded by laparoscopy. There were no cases of port site recurrence. Conclusion Diagnostic laparoscopy can be safely incorporated in the management of patients with peritoneal metastases, and can be especially beneficial in excluding patients from attempted incomplete cytoreduction. J. Surg. Oncol. 2015 111:1035–1040. © 2015 Wiley Periodicals, Inc.